Observed temperament from ages 6 to 36 months predicts parent- and teacher-reported attention-deficit/hyperactivity disorder symptoms in first grade. (11th January 2016) - Willoughby, Michael T.; Gottfredson, Nisha C.; Stifter, Cynthia A.; ,
Abstract: This study tested the prospective association between observational indicators of temperament, which were obtained across multiple assessments when children were 6–36 months of age, and parent and teacher reports of children's attention-deficit/hyperactivity disorder (ADHD) behaviors, when children were in first grade. Data were drawn from the Family Life Project and included 1, 074 children for whom temperament and either parent- or teacher-reported ADHD behavioral data were available. The results of variable-centered regression models indicated that individual differences in temperament regulation, but not temperamental reactivity, was uniquely predictive of parent- and teacher-reported ADHD behaviors. Latent profile analyses were used to characterize configurations of temperamental reactivity and regulation. Person-centered regression models were subsequently estimated in which temperamental profile membership replaced continuous indicators of temperamental reactivity and regulation as predictors. The results of person-centered regression models indicated that temperamental reactivity and regulation both contributed (both alone and in combination) to the prediction of subsequent ADHD behaviors. In general, the predictive associations from early temperament to later ADHD were of modest magnitude ( R 2 = .10–.17). Results are discussed with respect to interest in the early identification of children who are at elevated risk for later ADHD.